2011
DOI: 10.1603/an11086
|View full text |Cite
|
Sign up to set email alerts
|

Two Separate Introductions of Asian Citrus Psyllid Populations Found in the American Continents

Abstract: A phylogeographic analysis inferred from the partial mitochondrial cytochrome oxidase subunit I gene (433 bp) was performed with 22 populations of Diaphorina citri Kuwayama collected in the Americas and one in the Pacific. Eight populations from four countries in South America, 14 from four countries in North America, and one from Hawaii were analyzed. Twenty-three haplotypes (hp) were identified and they fell into two groups: hp1–8 were identified in South America (group 1) and hp9–23 were identified in North… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
43
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 30 publications
0
43
1
1
Order By: Relevance
“…Examination of mtCOI sequences revealed geographic patterns of D. citri and w Di populations that are in agreement with those of other studies. Comparison among mtCOI genes suggests two separate introductions of D. citri into the Americas, one in North America and the other in South America (de León et al ., ), while our data showed that the mtCOI sequences in these two areas are relatively different. The difference between mtCOI sequences from North America and Southeast Asia identified in our study was also concordant with patterns shown in other studies (Lashkari et al ., ).…”
Section: Discussioncontrasting
confidence: 61%
“…Examination of mtCOI sequences revealed geographic patterns of D. citri and w Di populations that are in agreement with those of other studies. Comparison among mtCOI genes suggests two separate introductions of D. citri into the Americas, one in North America and the other in South America (de León et al ., ), while our data showed that the mtCOI sequences in these two areas are relatively different. The difference between mtCOI sequences from North America and Southeast Asia identified in our study was also concordant with patterns shown in other studies (Lashkari et al ., ).…”
Section: Discussioncontrasting
confidence: 61%
“…Because of their relatively rapid rates of molecular evolution compared with nuclear loci, mitochondrial loci are often used to evaluate geographic variation in introduced species and to trace their movement and origins . The biodiversity of D. citri has been assessed in several regions using mitochondrial COI markers . Analyses of host mtDNA indicated a phylogeographical genetic break on the eastern Indian subcontinent and northwestern Indo‐Burma, forming the Western, Central and Eastern lineages, which correspond to geographically restricted P‐endosymbiont haplogroups.…”
Section: Discussionmentioning
confidence: 99%
“…Diaphorina citri is widely distributed in tropical and subtropical Asian countries, and is now also found in South, Central and North America, and East Africa . The biodiversity within D. citri from several regions has been identified through sequencing the mitochondrial COI gene, and using markers in the D. citri endosymbiont, Wolbachia wDi . Previous attempts to characterize biodiversity within accessions of D. citri across East and Southeast Asia used COI , but this marker does not explicitly incorporate geographic information .…”
Section: Introductionmentioning
confidence: 99%
“…DNA sequence data for the mitochondrial genes has been used to trace the origins and spread of a number of introduced insect pests ( Grapputo et al 2005;Corin et al 2007;Barr 2009;deLeón et al 2011;Auger-Rozenberg et al 2012), including H. halys Xu et al 2014;Cesari et al 2015). Previous genetic studies on H. halys from Asia and the USA have used the Cytochrome Oxidase II (COII) gene, coupled with the Cytochrome Oxidase I (COI) gene to narrow down the source region of the invasive US population (Xu et al 2014).…”
Section: Introductionmentioning
confidence: 99%